Some thoughts on the monitoring and preservation of waterlogged archeological sites in eastern England. (6th February 2017) - French, Charles
Abstract : This study reviews five hydrological monitoring projects used on archeological sites in the waterlogged landscapes of fenland East Anglia and east Yorkshire in England. The project design, recorded variables, and implications of each are discussed. In particular, the importance of understanding the landscape context is paramount, and retrieving an appropriate dataset over a sufficiently lengthy period of time to obtain reliable results and predictability. Some of the lessons learnt and outstanding problems are explored. As former wetlands are fast disappearing around the world through dewatering and a host of wider development threats such as urbanization and gravel extraction, the low intrusion suite of methods described here for measuring the degree and certainty of organic preservation is doubly important for establishing the viability of preservation in situ schemes for waterlogged archeological sites. This is crucial to get right, as wetland archeological records are an irreplaceable resource which offer extraordinarily full and diverse datasets of human lifeways which are all too often either poorly preserved or erroneously interpreted because of the skewed datasets recovered from dryland sites. WIREs Water 2017, 4:e1204. doi: 10.1002/wat2.1204 This article is categorized under: Science of Water > Methods Science of Water > Water and Environmental Change Human Water > Water as Imagined and Represented Abstract : This paper reviews the positives and negatives of five hydrological monitoring projects used on archaeological sites in the waterlogged landscapes of fenland East Anglia and east Yorkshire in England. The importance of understanding the landscape context is paramount, as is retrieving an appropriate dataset over a sufficiently lengthy period of time to obtain reliable results and predictability. This is crucial to get right as wetland archaeological records are an irreplaceable resource.